(untitled) (Bangladesh Journal of Pharmacology, 2015)
The objective was to determine the antiproliferative and apoptotic effects of theaflavin-3-gallate in human non-small cell lung cancer cells (A-549) along with determining the effect on cell cycle phase distribution, cell migration and invasion. Cell viability was determined by MTT assay while as phase contrast and fluorescence microscopies were involved to study apoptotic morphologi-cal features in these cells. Flow cytometry investigated the effect of theaflavin-3-gallate on cell cycle phase distribution. Theaflavin-3-gallate treatment led to a substantial cytotoxic effect in A-549 cancer cells with IC50 values of 42.1 µM and 27.9 µM at 24 and 48 hours respectively. Further, 80 and 160 µM dose of theaflavin-3-gallate induced apoptotic features including chromatin margina-tion and micronuclei presence. The population of cells in G2/M phase increased from 2.7% (control) to 6.8%, 17.2% and finally to 46.5% after treatment with 20, 80 and 160 µM concentration of theaflavin-3-gallate respectively indicating G2/M phase cell cycle arrest.